Overview of distribution patterns of zooxanthellate Scleractinia - Veron, John; Stafford-Smith, Mary; DeVantier, Lyndon; Turak, Emre (Frontiers in Marine Science, 2015)
This publication is an overview of a detailed study of coral distribution, diversity and affinities worldwide. The species distribution maps in www.coralsoftheworld.com are based on comprehensive global assessments of the world’s 150 coral ecoregions. Original surveys by the authors cover 4941 sites in 85 ecoregions worldwide. These are combined with a thorough summation of all biogeographic, taxonomic and related literature as well as an extensive review of museum and photographic collections worldwide and extensive inter-personal communications. Species occurrences in ecoregions are recorded as confirmed, strongly predicted, uncertain or absent. These data are used to present global maps of diversity and affinity at species level. There are two templates of Indo-Pacific diversity and affinity: one dominated by the Coral Triangle and one created by poleward continental boundary currents. There is a high degree of uniformity within the main body of the Coral Triangle; diversity and affinities both decrease in all directions. The Sunda Shelf ecoregion now qualifies for inclusion in the Coral Triangle and the Java Sea ecoregion is borderline. There is very little Indo-Pacific provincialism. Two separate centres of diversity occur in the Indian Ocean: the subequatorial west, and the Red Sea. Most species of the far eastern Pacific occur in the central Pacific. The Caribbean dominates Atlantic distribution and affinities and also has high uniformity. Individual ecoregions have very varying data comprehensiveness. Distribution patterns that distinguish between geographic variation within a species and the geographic overlap of sister species support the concept of reticulate evolution